Reflections on Christian-Muslim dialogue: the hermeneutics of messianism - Ucko, Hans (Islam and Christian-Muslim relations, 2009)
The article points to the dimension of waiting in Jewish, Christian and Shi‘a Muslim thinking as one particular feature of these traditions. There is a need to distinguish between escapist and productive eschatology. The whole question might also be a feature in a discussion on the interrelationship in international relations of the concepts of realism and idealism and the possible contribution of religion.